How to build a story (Assemble You, 2023)
Welcome to Audio Learning from Assemble You. We cover business storytelling, how to appeal to listeners, the importance of demonstrating transformation, and provide some tangible examples of where effective storytelling has been a success. Once you understand how stories are built, you'll become a much more confident presenter and writer. Learning Objectives Learn how to build a story using Situation, Complication and Resolution Learn how to structure a business story that engages customers in your company Learn how to get across messages of transformation and growth.